ANTIOXIDANT ACTIVITIES OF VARIOUS EXTRACTS FROM FIVE LEGUMES BEANS USING 2,2-DIPHENYL-1- PICRYLHYDRAZYL (DPPH) AND 2,2â-AZINO-BIS (3- ETHYLBENZTHIAZOLINE-6-SULFONIC ACID) (ABTS) METHODS - Elviana, Dilla
Many degeneratives related with the excessive of oxidation reaction in the body. The reactions lead to form actived free radical. Reactivity of free radical can be inhibited by antioxidant. Some of Fabaceae family including legumes had antioxidant activity. The aims of this research was to determine antioxidant activity of five legumes (soybean, green bean, peanut, red kidney bean and bogor peanut) by determining IC50 of DPPH (2,2-diphenyl-1-picrylhydrazyl) and IC50 of ABTS ((2,2’-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid)) of five legumes beans extracts; total phenolic, flavonoid and carotenoid content in various beans extracts of five legumes; correlation of total phenolic, flavonoid and carotenoid content with their IC50 of DPPH and IC50 of ABTS scavenging activities, and correlation of two antioxidant methods in sample extracts. Extraction was performed by reflux using various polarities solvents. Chromatogram pattern on each extract was observed by thin layer chromatography (TLC). Determination of IC50 of DPPH, IC50 of ABTS, total phenolic, flavonoid and carotenoid content was performed by UV-visible spectrophotometry and its correlation with IC50 of DPPH and IC50 of ABTS scavenging activities were analyzed by Pearson’s method. IC50 of DPPH of ethanolic extract of five legumes beans in the range of 3.13-29.28 µg/mL and IC50 of ABTS ranged from 1.26-37.42 µg/mL. The highest phenolic content was given by ethanolic extract of bogor peanut (3.04 g GAE/100 g), ethyl acetate extract of bogor peanut had the highest flavonoid content (8.69 QE/100 g) and ethanolic extract of peanut gave the highest carotenoid total (2.96 g BE/100 g). Phenolic total in red kidney bean extact had negatively high correlation with its IC50 of DPPH dan ABTS scavenging activities (p<0.01). IC50 of DPPH scavenging activities of red kidney bean and bogor peanut had positively high correlation with their IC50 of ABTS scavenging activities (p<0.01). Ethanolic extracts of soybean, green bean, peanut, red kidney bean and bogor peanut were categorized as very strong antioxidant. Phenolic compounds were major contributor in antioxidant activity of red kidney bean extract using DPPH and ABTS assays. Carotenoid compounds were the major contributor in antioxidant activity of green bean extract using DPPH assay. DPPH and ABTS methods gave linear results in red kidney bean and bogor peanut extracts.